Effect of reaction time and catalyst feed rate towards carbon nanotubes yields and purity by using rotary reactor - Rabita Firdaus,; Nur Syahidah Afandi,; Mehrnoush Khavarian,; Abdul Rahman Mohamed, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Continuous production of multi-walled carbon nanotubes (MWCNTs) by chemical vapor deposition (CVD) method was investigated in a rotary reactor. The aim of the study was to investigate the effect of catalyst feeding rate and reaction time on the MWCNTs production yield and purity. Bimetallic Co-Mo supported on MgO was used for the growth of MWCNTs and methane gas was used as the carbon precursor. The results indicated that the highest yield of MWCNTs production was attained at the reaction time of 180 min and catalyst feeding rate of 100 mg/min; this sample also had the highest purity (99.16%). SEM and TEM analyses of the synthesized product confirmed that most of the MWCNTs were sinuous and entangled with a uniform diameter. Raman spectroscopy indicated that the as-produced MWCNTs were mostly graphitic with few disordered carbon and impurities. The results highlighted that synthesized MWCNTs were highly pure which eliminates the need for MWCNTs purification process.